Media Pembelajaran Interaktif “SIBUDAYA” (Keragaman Budaya) Berbasis Self Instructional pada Muatan IPAS Kelas IV Sekolah Dasar - Aprilia, Ni Wayan Yeni; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the issue that the topic of cultural diversity in the IPAS subject at the elementary school level has a broad and complex scope, making it difficult for students to understand. This study aims to develop and test the effectiveness of an interactive learning media based on Self-Instructional principles. The development model used in this research is the ADDIE model, which consists of five stages. The research trial subjects comprised 32 fourth-grade elementary school students. The data analysis methods used include qualitative analysis, quantitative analysis, and inferential statistics to measure the effectiveness of the product. The feasibility test results of the interactive media